Case report: Cement entrapped in the inferior vena cava filter after pedicle screw augmentation - Han, Xinqiang; Zhang, Yongzhen; Wang, Zhu; Zhao, Mengpeng (Frontiers in Cardiovascular Medicine, 2022)
Background: Cement leakage into the inferior vena cava (IVC) is one of the most common complications associated with cement vertebroplasty, which can lead to potentially life-threatening complications such as pulmonary cement embolism. Implantation of an IVC filter is effective in the prevention of fatal pulmonary embolism. Here, we present an extremely rarely case of cement entrapped in IVC filter after pedicle screw augmentation, and discuss all similar cases reported in the literature. Case presentation: A 70-year-old female, who had significant back and lower extremities pain and was unable to walk. MRI of the lumbar spine revealed an osteoporotic compression fracture of the L1-L3. She underwent cement augmented pedicle screws implanted at the L1 and L3 vertebral bodies. A retrievable IVC filter was implanted due to the presence of calf veins thrombosis before cement vertebroplasty. Cement leakage into the IVC and trapped by the filter, rendering the filter unretrievable using a conventional method. The asymptomatic patient received rivaroxaban 20 mg daily for anticoagulant postoperatively and lifelong anticoagulation was administered to prevent secondary IVC and cemented filter thrombosis. Methods：A literature search was conducted utilizing the PUBMED/MEDLINE by using the following terms: “vertebroplasty”, “complication”, “bone cement”, and “inferior vena cava (IVC)” or “inferior vena cava (IVC) filter”. All relevant articles published in English or in other languages with English abstracts since 1962 were included. Results：A total of 36 articles were retrieved according to the search strategy. Only 6 out of these 36 studies contained information regarding the inferior vena cava filter and cement. 85.7% (36/42) of the patients, reported in the literature whose gender was known, were female and 14.3% were male. 28.5% (45/158) patients with pulmonary arterial and cardiovascular complications. Conclusion：Cement embolization occurs in the IVC filter is rare. Accurate knowledge about the lumbar vertebral venous anatomy and skillful operation during vertebral cementoplasty should be required in clinical practice.